2011
DOI: 10.1007/s00011-011-0409-3
|View full text |Cite
|
Sign up to set email alerts
|

The mast cell stabilizer ketotifen reduces joint capsule fibrosis in a rabbit model of post-traumatic joint contractures

Abstract: These data suggest an inflammatory pathway mediated by mast cell activation is involved in joint capsule fibrosis after traumatic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 35 publications
2
66
0
2
Order By: Relevance
“…Given such pharmacological properties of ketotifen, the administration of this drug could also be useful in the treatment of organ fibrosis in addition to its primary efficacy for allergic diseases. Recently, several animal studies have actually shown the therapeutic efficacy of ketotifen in the treatment of post-traumatic dermal or joint capsular fibrosis [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Given such pharmacological properties of ketotifen, the administration of this drug could also be useful in the treatment of organ fibrosis in addition to its primary efficacy for allergic diseases. Recently, several animal studies have actually shown the therapeutic efficacy of ketotifen in the treatment of post-traumatic dermal or joint capsular fibrosis [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of cardiac and peritoneal HO revealed presence of mast cells near sites of ectopic bone formation [41, 63]. Mast cells have also been shown to directly induce fibrosis following biomaterial scaffold implants in mice, indicating a more universal role of these cells in the overall wound repair process [56, 64, 65]. …”
Section: Innate Immunity and Heterotopic Ossificationmentioning
confidence: 99%
“…Also, body weight, diseases. Interestingly, it has been applied to non-allergic diseases, like improving sperm quality [10], irritable bowel syndrome [11] and reducing joint capsule fibrosis [12]. In addition, it has been suggested ketotifen has a novel medication for diabetes through stabilization of mast cells in animal model and human [13,14].…”
Section: Effect Of Ketotifen On Body Weight and Glucose Metabolismmentioning
confidence: 99%